Physical Exercise Decreases Endoplasmic Reticulum Stress in Central and Peripheral Tissues of Rodents: A Systematic Review - Matheus Santos de Sousa Fernandes; Georgian Badicu; Gabriela Carvalho Jurema Santos; Tayrine Ordonio Filgueira; Rafael dos Santos Henrique; Raphael Fabrício de Souza; Felipe J. Aidar; Fabrício Oliveira Souto; Patrícia Chakur Brum; Claudia Jacques Lagranha (MDPI AG, 2023)
Endoplasmic reticulum stress (ER stress) affects many tissues and contributes to the development and severity of chronic diseases. In contrast, regular physical exercise (PE) has been considered a powerful tool to prevent and control several chronic diseases. The present systematic review aimed to evaluate the impact of different PE protocols on ER stress markers in central and peripheral tissues in rodents. The eligibility criteria were based on PICOS (population: rodents; intervention: physical exercise/physical training; control: animals that did not undergo training; outcomes: endoplasmic reticulum stress; studies: experimental). The PubMed/Medline, Science Direct, Scopus, and Scielo databases were analyzed systematically. Quality assessment was performed using SYRCLE's risk of bias tool for animal studies. The results were qualitatively synthesized. Initially, we obtained a total of 2.490 articles. After excluding duplicates, 30 studies were considered eligible. Sixteen studies were excluded for not meeting the eligibility criteria. Therefore, 14 articles were included. The PE protocol showed decreased levels/expression of markers of ER stress in the central and peripheral tissues of rodents. PE can decrease ER stress by reducing cellular stress in the cardiac, brain, and skeletal muscle tissues in rodents. However, robust PE protocols must be considered, including frequency, duration, and intensity, to optimize the PE benefits of counteracting ER stress and its associated conditions.